Analisis Tindak Tutur Direktif dalam Daftar Putar Kok Bisa Explains: Your Introduction to Science pada Channel Youtube Kok Bisa? (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Pragmatics is an aspect of linguistics that examines the relationship between external context and the purpose of an utterance. Context plays a crucial role in understanding a speaker's intent when communicating with their interlocutor. This study aims to collect, analyze, and discuss various expressions found in educational playlist videos on the YouTube channel